Assessment of redox state and biochemical parameters of salivary glands in rats treated with anti-obesity drug sibutramine hydrochloride - dos Santos, Damáris Raissa [UNESP]; Fiais, Gabriela Alice [UNESP]; Oliveira, Henrique Arnaldo [UNESP]; Ribas, Tayná Buffulin [UNESP]; Souza, Rayne Oliveira [UNESP]; Tsosura, Thaís Verônica Saori [UNESP]; Matsushita, Doris Hissako [UNESP]; Ervolino, Edilson [UNESP]; Dornelles, Rita Cássia Menegati [UNESP]; Nakamune, Ana Cláudia de Melo Stevanato [UNESP]; Chaves-Neto, Antonio Hernandes [UNESP] (Springer Nature, 2022)
Objectives: To investigate the effects of anti-obesity drug sibutramine hydrochloride (SB) on redox state and biochemical parameters in the salivary glands. Materials and methods: Adult male Wistar rats were randomly divided into the following groups (n = 8 per group): control rats treated with vehicle (C) and rats treated with SB (10 mg/kg/day) by intragastric gavage for 28 days. The parotid (PG) and submandibular (SMG) glands were processed using histomorphometric analysis, and total protein, amylase, mucin, and oxidative damage to lipids were determined by measuring the formation of thiobarbituric acid reactive substances (TBARS), total antioxidant capacity (TAC), uric acid (UA), total glutathione (tGSH), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), and AKT phosphorylation. Results: SB decreased the acinar area, and increased the stromal area in PG, while no effect on the morphometric parameters was observed in SMG. SB also increased oxidative damage to lipids (TBARs). The SB group showed lower total protein, amylase, TAC, UA, tGSH, SOD, CAT, and GPx than the C group in PG, while in SMG, SB decreased total protein, mucin, tGSH, SOD, CAT, and GPx. However, increased AKT phosphorylation observed in both salivary glands suggests that SB exerts low-intensity oxidative stress. Conclusions: SB impaired enzymatic and non-enzymatic antioxidant defenses in the salivary glands of rats. Clinical relevance: Chronic treatment with SB could mitigate salivary gland dysfunction due to disturbance of redox state.
Keywords: Anti-obesity agents; Oxidative stress; Parotid gland; Sibutramine hydrochloride; Submandibular gland